DIVERSITY, THREATS AND CONSERVATION OF CATFISH (ORDER SILURIFORMES) FROM SUB BASIN OF WAINGANGA RIVER NEAR ARMORI, DISTRICT GADCHIROLI, MAHARASHTRA, INDIA - ABHAY D. TALMALE; DEEPAK S. BANSOD; SUNIL S. CHAUDHARI; GUNWANT G. WADPALLIWAR (The Bioscan, 2025)
The present study of catfish was carried out from the Wainganga River sub basin of Armoritaluka, District Gadchiroli, Maharashtra, India. It has been carried out to explore the diversity, threats and conservation status of catfish. The study was conducted from November 6, 2023, to October 5, 202 4. The documented paper deals with the variety, Abundance, threats, and conservation status (IUCN) of Catfish. The study was conducted between the range of 15 km. In present study, 13 species belonging to the Order Siluriformes with 7 families and 9 genera are reported. The dominant family among the catfish family was Bagridae (46.15 %) with 6 species, Siluridae (15.38%) with 2 species, Clariidae (7.69%), Pangasiidae (7.69%), Schilbeidae (7.69%), Sisoridae (7.69%), and Heteropneustidae (7.69%) with each 1 s pecies recorded. (Graph No.1) In the variety of catfish found, 8 species were common, 1 species was uncommon, 2 species were occasional, and 2 species were rare. According to IUCN status, 10 species were in the least concern category, while 3 species were in the Near Threatened (NT) category. The distribution of catfish along the Wainganga River system may be due to slow and stable state of water movement and its width ensures the continuous availability of nutrition. It is suggested that the Wainganga Rive r would be a suitable habitat for the conservation of freshwater catfish if the threats are diminished.